Evaluation of the Cytotoxic Activity of Some Brazilian Medicinal Plants - Ribeiro, Sandra S.; de Jesus, Aline M.; dos Anjos, Charlene S.; da Silva, Thanany B.; Santos, Alan D. C.; de Jesus, Jemmyson R.; Andrade, Moacir S.; Sampaio, Tais S.; Gomes, Wesley F.; Alves, Péricles B.; Carvalho, Adriana A.; Pessoa, Claudia; de Moraes, Manoel O.; Pinheiro, Maria L. B.; Prata, Ana Paula N.; Blank, Arie F.; Silva-Mann, Renata; Moraes, Valeria R. S.; Costa, Emmanoel V.; Nogueira, Paulo Cesar L.; Bezerra, Daniel P. (Planta Medica, 2012)
Plants are promising sources of new bioactive compounds. The aim of this study was to investigate the cytotoxic potential of nine plants found in Brazil. The species studied were: Annona pickelii Diels (Annonaceae), Annona salzmannii A. DC. (Annonaceae), Guatteria blepharophylla Mart. (Annonaceae), Guatteria hispida (R. E. Fr.) Erkens & Maas (Annonaceae), Hancornia speciosa Gomes (Apocynaceae), Jatropha curcas L. (Euphorbiaceae), Kielmeyera rugosa Choisy (Clusiaceae), Lippia gracilis Schauer (Verbenaceae), and Hyptis calida Mart. Ex Benth (Lamiaceae). Different types of extractions from several parts of plants resulted in 43 extracts. Their cytotoxicity was tested against HCT-8 (colon carcinoma), MDA-MB-435 (melanoma), SF-295 (glioblastoma), and HL-60 (promielocitic leukemia) human tumor cell lines, using the thiazolyl blue test (MTT) assay. The active extracts were those obtained from G. blepharophylla, G. hispida, J. curcas, K. rugosa, and L. gracilis. In addition, seven compounds isolated from the active extracts were tested; among them, β-pinene found in G. hispida and one coumarin isolated from K. rugora showed weak cytotoxic activity. In summary, this manuscript contributes to the understanding of the potentialities of Brazilian plants as sources of new anticancer drugs.
Keywords: cytotoxicity; Guatteria blepharophylla; Guatteria hispida; Jatropha curcas; Kielmeyera rugosa; Lippia gracilis; extracts; essential oil